2001
DOI: 10.1063/1.1329343
|View full text |Cite
|
Sign up to set email alerts
|

Melting/freezing behavior of a fluid confined in porous glasses and MCM-41: Dielectric spectroscopy and molecular simulation

Abstract: We report both experimental measurements and molecular simulations of the melting and freezing behavior of fluids in nanoporous media. The experimental studies are for nitrobenzene in the silica-based pores of controlled pore glass, Vycor, and MCM-41. Dielectric relaxation spectroscopy is used to determine melting points and the orientational relaxation times of the nitrobenzene molecules in the bulk and the confined phase. Monte Carlo simulations, together with a bond orientational order parameter method, are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
95
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(114 citation statements)
references
References 54 publications
19
95
0
Order By: Relevance
“…[1][2][3][4][5][6] Extensive studies of constrained species also indicate that the final behavior of the adsorbate depends on the interaction between the particles and the confining walls. [7][8][9][10] However, this is only a part of the problem since simulation results also suggest that in order to describe completely the involved phenomenology, one should take into account not only the energetics of the considered arrangement but also the steric influence of pure confinement in the properties under scrutiny. 11 In systems with soft attractive and repulsive interactions, such as Lennard-Jones-type adsorbates inside a carbon nanotube or a silica pore, the energetic and the entropic influences compete to produce a net effect whose relative contributions cannot be easily separated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Extensive studies of constrained species also indicate that the final behavior of the adsorbate depends on the interaction between the particles and the confining walls. [7][8][9][10] However, this is only a part of the problem since simulation results also suggest that in order to describe completely the involved phenomenology, one should take into account not only the energetics of the considered arrangement but also the steric influence of pure confinement in the properties under scrutiny. 11 In systems with soft attractive and repulsive interactions, such as Lennard-Jones-type adsorbates inside a carbon nanotube or a silica pore, the energetic and the entropic influences compete to produce a net effect whose relative contributions cannot be easily separated.…”
mentioning
confidence: 99%
“…16 Nevertheless, there is profuse information about transitionlike transformations in narrow tubes. [5][6][7][8][9][10] Transformations in confined systems resembling the bulk liquid-solid phase transitions are commonly referred to as "freezing." 1 In this paper, freezing represents then a behavior qualitatively similar to a solid-liquid transition ͑driven by temperature changes or by purely geometrical packing effects͒, but in a context in which the existence of a real transition is not formally possible or cannot be demonstrated.…”
mentioning
confidence: 99%
“…The state of the IBU crystallites trapped in the lumen of halloysite could be evaluated on the basis of the study by Sliwinska-Bartkowiak et al [58]. In this study, both experiments and molecular simulations of a crystallization study of nitrobenzene fluids in a confined space of porous glasses and MCM-41 suggested that the guest fluid was crystallized in the presence of pores with average diameters larger than 20r, where r is the diameter of the guest molecule.…”
Section: Characterization Of the Aptes-modified And Ibu-loaded Halloymentioning
confidence: 95%
“…The fast spin lattice relaxation rates ($1 ms) of the 23 Na nuclei, as well as the low sensitivity of the 13 C nuclei, prevent the use of 2D chemical exchange NMR experiments, which should be able to address this point. Future work on 13 C, 15 N isotopically labelled composites studied at variable temperatures should bring about more quantitative insights into the dynamics of the conned complexes.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 According to a study combining Dielectric Relaxation Spectroscopy and Differential Scanning Calorimetry experiments with Grand Canonical Monte Carlo simulations, 15 uids conned in cylindrical nanopores (e.g. MCM41) should freeze into a single crystalline structure for average pore diameters larger than 20s (s being the diameter of the guest molecule).…”
Section: 12mentioning
confidence: 99%